Supplementation of Corriente steers stocked on bermudagrass pastures sod‐seeded with rye–ryegrass before the feedlot period. Issue 1 (23rd February 2022) - Rouquette, Francis Monte; Norman, Kelli D.; Long, Charles
Core Ideas: Crossbreds had greater average daily gain (ADG) off rye–ryegrass than Corrientes. Supplementation with 2 lb d –1 corn on rye–ryegrass increased ADG for crossbreds. Supplementation with corn–fishmeal increased the ADG of Corrientes on bermudagrass. In the feedlot, Corrientes had lower ADG and higher feed/gain ratios than crossbreds. The best management strategy for Corrientes was pasture without a feedlot period.